2005
DOI: 10.1074/jbc.m506623200
|View full text |Cite
|
Sign up to set email alerts
|

The Type III Inositol 1,4,5-Trisphosphate Receptor Preferentially Transmits Apoptotic Ca2+ Signals into Mitochondria

Abstract: There are three isoforms of the inositol 1,4,5-trisphosphate receptor (InsP 3 R), each of which has a distinct effect on Ca 2؉ signaling. However, it is not known whether each isoform similarly plays a distinct role in the activation of Ca 2؉ -mediated events. To investigate this question, we examined the effects of each InsP 3 R isoform on transmission of Ca 2؉ signals to mitochondria and induction of apoptosis. Each isoform was selectively silenced using isoform-specific small interfering RNA in Chinese hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
224
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 253 publications
(236 citation statements)
references
References 55 publications
8
224
1
3
Order By: Relevance
“…21,30,31 Our results show that GSK3β preferentially interacts with IP 3 R1, and can also interacts with IP 3 R2 and IP 3 R3 in cardiac cells (data not shown). In summary, we propose that inhibition of GSK3β might decrease the phosphorylation and the activity of IP 3 R, thereby limiting cytosolic and mitochondrial Ca 2+ overload, possibly contributing to the reduction of both cell death and infarct size at reperfusion.…”
Section: Discussionmentioning
confidence: 69%
“…21,30,31 Our results show that GSK3β preferentially interacts with IP 3 R1, and can also interacts with IP 3 R2 and IP 3 R3 in cardiac cells (data not shown). In summary, we propose that inhibition of GSK3β might decrease the phosphorylation and the activity of IP 3 R, thereby limiting cytosolic and mitochondrial Ca 2+ overload, possibly contributing to the reduction of both cell death and infarct size at reperfusion.…”
Section: Discussionmentioning
confidence: 69%
“…[26][27][28][29] To investigate a possible mechanism for ER-PTEN action, we looked for a physical interaction between PTEN and IP3R3, as release of the ER Ca 2 þ through IP3R3 appears to sensitize cells to apoptotic stimuli. 24,30 We performed co-immunoprecipitation experiments of proteins extracted from the ER fraction in basal condition or after ArA treatment, and found that PTEN co-immunoprecipitated with IP3R3, together with Akt, a known iteractor and modulator of IP3R-mediated Ca 2 þ release from the ER. 19 Akt-dependent inhibition of Ca 2 þ transfer from the ER to mitochondria, through IP3R3 phosphorylation, protects from Ca 2 þ -mediated apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Potential target sites within the rat InsP3R genes were selected and then searched with NCBI BlastN to confirm specificity for each InsP3R isoform as described previously (13). The siRNAs for the type I, II, and III InsP3R were prepared by a transcription-based method using the Silencer kit according to the manufacturer's instruction (Ambion, Austin, TX).…”
Section: Sirna Studiesmentioning
confidence: 99%
“…The sense and antisense oligonucleotides of siRNAs were, respectively, as follows: type I, 5′-AAAGTTGTAGCTGCTGGTGCTCCTGTCCTC-3′ and 5′-AAAGCACCAGCAG CTACAACTCCTGTCCTC-3′; type II, 5′ -AACAGCCTAATCAAGATCTCCCCTG TCTC-3′ and 5′-AAGGAGA TCTTGATTAGGCTGCCTGTCTC-3′; type III, 5′-ATGGTGCTGGCAAACTTGTTTCCTGTCCTC-3′ and 5′ -AAACAAGTTTGCCA GCACCATCCTGTCCTC-3′; scrambled (siRNA negative control), 5′-AACACCTATAACAACGGTAGTC CTGTCTC -3′ and 5′-AAACTACCGTTGTTATAGGTGCCTGTCTC -3′. siRNA constructs were tested for efficacy in CHO cells as described previously (13) and then used in IBDUs (14). IBDUs were maintained in culture with siRNAs or the corresponding scrambled siRNA for 24 hr at 37°C prior to use in microperfusion studies.…”
Section: Sirna Studiesmentioning
confidence: 99%